212Pb: Production Approaches and Targeted Therapy Applications - Konstantin V. Kokov; Bayirta V. Egorova; Marina N. German; Ilya D. Klabukov; Michael E. Krasheninnikov; Antonius A. Larkin-Kondrov; Kseniya A. Makoveeva; Michael V. Ovchinnikov; Maria V. Sidorova; Dmitry Y. Chuvilin (MDPI AG, 2022)
Over the last decade, targeted alpha therapy has demonstrated its high effectiveness in treating various oncological diseases. Lead-212, with a convenient half-life of 10.64 h, and daughter alpha-emitter short-lived 212Bi (T1/2 = 1 h), provides the possibility for the synthesis and purification of complex radiopharmaceuticals with minimum loss of radioactivity during preparation. As a benefit for clinical implementation, it can be milked from a radionuclide generator in different ways. The main approaches applied for these purposes are considered and described in this review, including chromatographic, solution, and other techniques to isolate 212Pb from its parent radionuclide. Furthermore, molecules used for lead's binding and radiochemical features of preparation and stability of compounds labeled with 212Pb are discussed. The results of preclinical studies with an estimation of therapeutic and tolerant doses as well as recently initiated clinical trials of targeted radiopharmaceuticals are presented.